JALINAN KOMUNIKASI UNTUK MEWUJUDKAN KETAHANAN PANGAN SORGUM DI KAMPUNG SORGUM LIKOTUDEN - Yanto, Marianus Diaz; Pawito, Pawito; Rahmanto, Andre Noevi (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
Intensive and equitable communication is an important method of persuasion for food diversification. Cooperation between institutions is important to realize the idea of food security in the regions, because the regions are the embodiment of the concept of national food security. One of these agendas was carried out in Likotuden village by farmer groups together with NGOs. In it, cooperation and relations with the government are established. The purpose of this study is to explain the communication that occurs in Likotuden sorghum village related to sorghum food security. This research is a qualitative research with a case study method. The results of the study show that there has been communication in Likotuden Village to realize food security. The communication established between NGOs and community groups that are members of the Herin Lela sorghum farmer group plays an important role in helping farmers to be independent in food security and household economic security.